PENGARUH PEMBANGUNAN INFRASTRUKTUR DASAR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Suriani Suriani; Cut Nanda Keusuma (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study aimed to analyzed the effect of the construction of basic infrastructure for economic growth in 26 provinces by using secondary data from 2004 – 2009. The model used is multiple linear regression using Panel Data with  Fixed Effect Analysis Method. The results of this study show variable electricity and roads in a positive and significant effect on economic growth in the region in 26 provincial in Indonesia. The provincial government is expected to prioritize the allocation of funds for the improvement of access to basic infrastructure (roads, electricity, telephone, and water), especially in remote areas, so as to boost economic growth in each province in Indonesia. Keywords: economicgrowth, basic infrastructur, data pael, FEM